2018
DOI: 10.1371/journal.pone.0203287
|View full text |Cite
|
Sign up to set email alerts
|

Attachment buffers the physiological impact of social exclusion

Abstract: Attachment systems facilitate coping with stress, with previous studies demonstrating attachment figures diminishing subjective, behavioral and neural responses to social pain. Yet little is known about the physiological mechanisms governing this benefit in the context of social exclusion. This study investigated the impact of attachment (vs non-attachment) priming on affective and cardiovascular responses to social exclusion induced by the computerized “Cyberball” ball-tossing game, and the moderating influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 49 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…Outliers were then replaced by either the maximum (three standard deviations above the mean) or minimum integer (three standard deviations below the mean; comprising 1.89% of the total transformed data). This method is commonly used in psychophysiological studies to prevent outliers from unduly influencing statistical outcomes but also to retain the overall distribution in the data (Howell, 1998; Laborde et al, 2017; Liddell and Courtney, 2018). Next, difference scores were calculated for HF-HRV and HR comparing each of the active phases to the baseline phase (prime phase = priming phase – baseline; emotion reactivity phase = image exposure phase – baseline; and recovery phase = recovery phase – baseline).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outliers were then replaced by either the maximum (three standard deviations above the mean) or minimum integer (three standard deviations below the mean; comprising 1.89% of the total transformed data). This method is commonly used in psychophysiological studies to prevent outliers from unduly influencing statistical outcomes but also to retain the overall distribution in the data (Howell, 1998; Laborde et al, 2017; Liddell and Courtney, 2018). Next, difference scores were calculated for HF-HRV and HR comparing each of the active phases to the baseline phase (prime phase = priming phase – baseline; emotion reactivity phase = image exposure phase – baseline; and recovery phase = recovery phase – baseline).…”
Section: Methodsmentioning
confidence: 99%
“…If HRV is low, this indicates a system that is less adaptive with reduced regulation capacity. In experimental studies, measuring HRV is a useful indicator of the physiological benefit of engaging in various ER strategies (Appelhans and Luecken, 2006; Denson et al, 2011; Quintana et al, 2012; Geisler et al, 2013; Liddell and Courtney, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, low HF HRV was associated with negative affect in a large study (Sloan et al, 2017) and HF HRV was found to decrease in response to stressful situations (Balzarotti et al, 2017). Given that decreased HF HRV has been used as an index of negative emotionality or distress in various contexts (including Collective narcissism and distress of exclusion interpersonal exclusion research relevant to this article, Liddell & Courtney, 2018), we used this psychophysiological index in our study.…”
Section: Present Studymentioning
confidence: 99%
“…One review ( 12 ) also demonstrated that social support has been associated with lower levels of perceived physical pain. As it is known that dimensions of insecure attachment moderate the relationship between social support and (mental and physical) health ( 54 , 55 ), the attachment patterns should be considered according to the therapeutic treatment. Furthermore, insecure-attached individuals are sensitive to social rejection, regardless of the presence of SPD.…”
Section: Clinical Implications and Conclusionmentioning
confidence: 99%